Expression of segment a gene of UPM04/190 infectious bursal disease virus in Arabidopsis thaliana - Liew, Pit Sze; Omar, Abdul Rahman; Ideris, Aini; Bejo, Mohd Hair (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
Infectious bursal disease (IBD), which is caused by the IBD virus (IBDV), has been a great concern for the Malaysian poultry industry. The use of the whole IBDV genome segment A in vaccine preparation may have better potential for full protection against IBDV infection due to the viral multigenic nature of virulence. Therefore, the present study was conducted to determine the feasibility of expressing the whole IBDV genome segment A in the laboratory model plant Arabidopsis thaliana. The characterised segment A gene of UPM04/190 IBDV isolate was cloned into a binary vector and used to stably transform A. thaliana Col-1 by the Agrobacterium-mediated floral dip method. Analysis on the transgenic A. thaliana by PCR detection showed the presence of IBDV segment A-specific transgene DNA, while hybridization of the total plant protein extracts with polyclonal IBDV antibody revealed the accumulation of IBDV VP2 protein. These findings confirmed the successful transformation of A. thaliana and expression of IBDV protein in transgenic plants, and demonstrated a promising future of plant expression system for the development of plant-based poultry vaccines.